Análise dos efeitos da política monetária sobre a persistência inflacionária no Brasil - Zuffo, Vicente Matheus Moreira (2015)
This work aims to analyze the relationship between monetary policy and inflation persistence in recent years, after the introduction of the inflation targeting regime in Brazil. Through a simplified new-Keynesian model, the degree of inflation-gap persistence is modeled as a function of the monetary policy rule weights. The time-varying Taylor rule is confronted with the estimated curve of inflation-gap persistence, demonstrating that changes in monetary policy lead to changes in the level of inflation persistence in the economy. An adaptation of the model with a Taylor rule that incorporates the output gap expectations, reaches the same results more accurately.